Revealing the potential of squid chitosan-based structures for biomedical applications - Reys, L. L. (2013)
In recent years, much attention has been given to different marine organisms, namely as potential sources of valuable materials with a vast range of properties and characteristics. In this work, β-chitin was isolated from the endoskeleton of the giant squid Dosidicus gigas and further deacetylated to produce chitosan. Then, the squid chitosan was processed into membranes and scaffolds using solvent casting and freeze-drying, respectively, to assess their potential biomedical application. The developed membranes have shown to be stiffer and less hydrophobic than those obtained with commercial chitosan. On the other hand, the morphological characterization of the developed scaffolds, by SEM and micro-computed tomography, revealed that the matrices were formed with a lamellar structure. The findings also indicated that the treatment with ethanol prior to neutralization with sodium hydroxide caused the formation of larger pores and loss of some lamellar features. The in vitro cell culture study has shown that all chitosan scaffolds exhibited a non-cytotoxic effect over the mouse fibroblast-like cell line, L929 cells. Thus, chitosan produced from the endoskeletons of the giant squid Dosidicus gigas has proven to be a valuable alternative to existing commercial materials when considering its use as biomaterial.